Foliar Application of Spermidine Reduced the Negative Effects of Salt Stress on Oat Seedlings - Hai, Xia; Mi, Junzhen; Zhao, Baoping; Zhang, Biru; Zhao, Zhou; Liu, Jinghui (Frontiers in Plant Science, 2022)
The effects of foliar application of spermidine (Spd) on the physiological aspects of salt-stressed oat seedlings were studied under greenhouse conditions. At the seedling stage, the salt-sensitive variety, namely, Caoyou 1 and the salt-tolerant variety, namely, Baiyan 2 were treated with 70 and 100 mM of salt, followed by the foliar application of 0.75 mM Spd or distilled water. Results showed that Spd application increased the activities of superoxide dismutase (SOD), peroxidase (POD), catalase (CAT), and ascorbate peroxidase (APX), and reduced the rate of O2⋅– production and the accumulation of H2O2 and malondialdehyde (MDA). In addition, it increased the level of zeatin riboside (ZR) and the content of endogenous polyamines. The application of Spd increased the contents of soluble sugar, soluble protein, and free proline and helped maintain the osmotic balance of oat leaves. At the same time, foliar Spd treatment helped in maintaining the ion nutrition balance. Specifically, it reduced the content of Na+ and thereby stabilized the ratio of Na+/K+, Na+/Ca2+, and Na+/Mg2+. The effects of Spd application were more obvious for the salt-sensitive cultivar Caoyou 1 and under the lighter 70 mM salt stress.